14 Understanding patients' perspectives of spirituality to inform care at the end of life: a qualitative systematic review. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Clyne, Barbara; O'Neill, Sinead M; O'Neill, Michelle; Larkin, James; Ryan, Mairin; Smith, Susan M
Abstract : Objectives: Caring for a patient's spiritual needs is well recognised as an important facet of patient care, particularly in the provision of end of life care. Understanding patient perceptions of their spiritual needs when approaching the end of life is essential to support the delivery of patient-centred care. The aim of this study was to conduct a systematic review of qualitative literature on spirituality and spiritual care needs at the end of life from the patients' perspective to inform the development of a National Clinical Effectiveness Committee (NCEC) national clinical guideline for care of the dying adult in the Republic of Ireland. Method: A systematic search of five databases (including Medline and Applied Social Science Index and Abstracts) was conducted from inception until January 2019 using a comprehensive search strategy. Studies were included where they were primary qualitative studies exploring spirituality (defined as a search for meaning and purpose, which may or may not include reference to the divine) in patients with a life expectancy of 12 months or less in any setting. Two reviewers independently screened titles using Covidence software, extracted data in standardised forms, and conducted methodological quality appraisal (using the Critical Appraisal Skills Programme checklist). A thematic synthesis of included studies was conducted, using line by line coding, developing descriptive and analytical themes using NVivo 12 software. The GRADE-CERQual (Confidence in the Evidence from Reviews of Qualitative research) approach was used to summarise the certainty of the evidence. Results: Forty-seven papers, describing 42 unique datasets, incorporating data from 710 patients were included. The study recruited from a mix of inpatient, outpatient, hospice and community settings across 12 different countries with 49% of studies conducted in the US. Preliminary findings demonstrate spirituality was expressed both through religious practices, and through relationships or connectedness with family, friends, nature and with a sense of self. Spirituality has on-going importance to those at the end of life as a means of finding hope, meaning and certainty, living remaining life well and adjusting to dying. Considering the broad sense of spirituality expressed by participants, practice improvements may include healthcare providers acknowledging and supporting patients' desires for creating meaning, purpose and connectedness through listening, connecting, and engaging in discussions about these needs. Greater access to chaplains for participants who expressed spirituality through religion may also be of benefit. Conclusions: Qualitative research is increasingly used in the development of evidence-based health care and clinical guidelines. Such methodologies provide deeper insights into patient experiences of healthcare services and ill-health and support the provision of healthcare that is more patient-centred. The findings from this systematic review highlight the importance of spirituality for patients at the end of life as means of finding hope, meaning and certainty, living remaining life well and adjusting to dying. These findings will be used to inform the development of a national clinical guideline for care of the dying adult in the Republic of Ireland. PROSPERO: The protocol for this systematic review was registered on PROSPERO, CRD42019122062